Valorization of grape seed waste for use in the production of antioxidant soaps and as an adsorbent for a textile dye - Gonzales-Condori, Elvis Gilmar; Gutiérrez-Delgado, Joan Anderson; Bejar-Aramburú, Dalescka G.; Zúñiga Torres, Juan Carlos; Cama-Ortiz, Fanny; Gonzales-Condori, Jonathan; Alvarez-Gonzales, Rosa (LACCEI, 2023)
In most cases, waste from the wine industry is wasted, generating environmental pollution. For this reason, the objective of this research was to prepare soaps from the oil of these seeds for subsequent determination of the antioxidant capacity by the 2,2-Diphenyl-1-picrylhydrazyl (DPPH) assay, and with the residues generated from the extraction of the oil, the adsorbent potential of this residue for an anionic textile dye was evaluated. The results showed that the prepared liquid soap presented an antioxidant capacity corresponding to an IC50 of 3.33%. Higher antioxidant capacity was obtained in the solid soap with an IC50 of 0.075%. After the adsorption study of the anionic green acid dye 25 (AG25) with defatted grape seed residues, it was possible to remove 100% of the color from water contaminated with AG25 at a concentration of 30 mg/L at pH=2, a dosage of 0.5 g/L, and an agitation speed of 300 rpm for 120 minutes. The pseudo second order kinetic model was a better fit for the dye removal process thus evidencing that the adsorption mechanism involved is chemisorption. The results of the FTIR-ATR analysis showed that the original grape residue has OH, C-H, and C=O groups that are characteristic of the presence of oil in the seed, and after oil extraction the intensity of the vibrations of the C=O and C-H groups are reduced because the residue was defatted. After the adsorption of AG25, the C-H vibration became less intense. Finally, the point of zero charge of the grape seed variety Italia was 4.67, so the interaction between adsorbate-adsorbent would correspond to electrostatic attractions. The present study has shown that the grape seed variety Italia is a waste with biorefinery potential as it possesses antioxidant compounds found in soaps, which could economically benefit the wine industries, and at the same time, the degreased waste has a high capacity to remove dyes, being an environmentally friendly alternative that can be considered for the treatment of textile wastewater.